Lattice determinations of the strange quark mass - RYAN, SINEAD MARIE (University of Chicago, 1999)
The importance of the strange quark mass, as a fundamental parameter of the Standard Model (SM) and as an input to many interesting quantities, has been highlighted in many reviews, eg in Ref . A first principles calculation of ms is possible in lattice QCD but to date there has been a rather large spread in values from lattice calculations. This review aims to clarify the situation by explaining the particular systematic errors and their effects and illustrating the emerging consenus.
Conference on Kaon Physics (K 99), [FERMILAB-CONF-99/222-T]
PUBLISHED
Keywords: Pure & Applied Mathematics